Effect of reduced graphene oxide on the thermoelectric properties of titanium dioxide: Seebeck coefficient analysis - Kahawaththe, K. G. D. T. B.; Narangammana, L. K.; Bandara, T. M. W. J.; Subasinghe, N. D. (Faculty of Science, University of Kelaniya Sri Lanka, 2024)
Researchers worldwide are more focused on finding new ways to utilize waste energy to address increasing global energy demand. Thermoelectricity has attracted significant interest because it can generate electric energy using this waste heat energy. Thermoelectric energy recovery at a temperature range close to the ambient has attracted significant interest because of the usage of numerous heat sources near room temperature such as consumer electronics, solar cells, home heating and wearable devices on human bodies. The properties of thermoelectric materials (TEs) are typically characterized by their figure of merit, Seebeck coefficient, electrical conductivity and thermal conductivity. The conventional TEs such as bismuth and antimony chalcogenide-based materials were toxic and expensive. Therefore, in this study, the thermoelectric properties of nontoxic titanium dioxide (TiO2) were investigated. In order to prepare the TiO2 pellets, RGO and TiO2 were mixed in a mass percentage of 0%, 1%, 3% and 5% was mixed anhydrous acetonitrile using the mortar and pestle until they became fine powder. A compressive force of 40 kN, resulting in a pressure of 301 MPa, was applied for 5 to 7 minutes to prepare the pellets, which have a diameter of 13 mm and a thickness of 4 mm. The pellets were then annealed at 650 °C for approximately 30 minutes. Generated voltages were measured and the Seebeck coefficient was calculated for RGO-added TiO2 pellets by varying the temperature. RGO incorporation improved the Seebeck coefficient of TiO2 pellets and the Seebeck coefficient values were negative over the entire temperature range studied, indicating n-type conduction of this TE material (TEM). The generated voltages of 0%, 1%, 3% and 5% RGO- TiO2 pellets at 373 K were 3.97±0.02, 5.15±0.03, 8.43±0.05 and 7.19±0.04 mV respectively and Seebeck coefficients at 373 K were -0.18±0.01, -0.24±0.01, -0.41±0.02 and -0.36±0.01 mV K-1 respectively. The results indicate that the highest Seebeck coefficient and the maximum generated voltage were observed for the 3% RGO added sample. To the best of our knowledge thermoelectric parameters of bulk TiO2 have not been reported before. This novel TEM shows promising thermoelectric properties and the results indicate that TiO2 is better TEM compared to the widely studied ZnO.
Keywords: Thermoelectric materials, Seebeck effect, Titanium dioxide, generated voltage.